Penerapan Konseling Kelompok Untuk Mengurangi Kecanduan Game Online Pada Siswa - Azka, Nawalul; Muslima; Arliani, Desi (JURNAL ILMIAH MAHASISWA, 2024)
Online game addiction is a form of addiction caused by internet technology which makes a person very attached to playing online games, from time to time there will be an increase in frequency and duration. Online games are games that are very popular and popular among teenagers, including students. Online games have a bad influence on students if they are played for an excessive amount of time so that addiction to online games causes students to reduce their study time. The aim of this research is to determine the reduction of online game addiction through group counseling services for students. The method in this research uses a quantitative approach with a One Group Pretest and Posttest design. The research sample consisted of 5 students based on the recommendation of the guidance and counseling teacher using purposive sampling technique. The data collection technique uses a questionnaire to measure students' level of online game addiction. The research results showed that there was a significant reduction after providing treatment through group counseling in the level of online game addiction with a calculated t value of 20,250 which was greater than the t table of 2,131 (20,250>2,131). This means that the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. It can be concluded that research shows that the application of group counseling can reduce online game addiction in students